CLINICAL THERAPEUTIC AND ADJUVANT CONDUCT IN ALCOHOLIC HEPATITIS: CLINICAL THERAPEUTIC AND ADJUVANT CONDUCT IN ALCOHOLIC HEPATITIS - Feitosa, Ankilma do Nascimento Andrade; Moraes, Carlos Américo da Costa; Nascimento, Ingridy Michely Gadelha do; Alencar Neta, Raimunda Leite de; Brito, Luciana Modesto de; Sarmento , Thaise de Abreu Brasileiro (Brazilian Journal of Production Engineering, 2020)
Alcoholic liver disease one of the worst problems arising from alcohol abuse. It is manifested by liver sequelae, as: steatosis, hepatitis, fibrosis and cirrhosis. The objective of the study is identify which medications and conducts have proven benefits in the treatment of AH. An integrative review was carried out, based on the guiding question: which medications and conduct shave proven benefits in the treatment of alcoholic hepatitis? The search for the articles place in LILACS, SCIELO and MEDLINE using descriptors registered in the DeCS: Alcoholic Liver Disease, Treatment and Alcoholic Hepatitis. The inclusion criteria: full texts, human studies, guidelines, cohort studies, clinical trials, systematic, integrative reviews and meta-analysis, in the last 10 years. Studies shown that alcohol cessation is the first and most important measure in the management of alcoholic hepatitis. Corticosteroids remain a primary drug option to treat alcoholic hepatitis. Pentoxifylline, although used in cases that culminate in hepatorenal syndrome, has questionable benefits. Early liver transplantation is indicated when there is no response to corticosteroids. There are adjuvant medications such as antidepressants and anticonvulsants in the context of treatment against alcohol abuse. The management of alcoholic hepatitis in the emergency department requires a multidisciplinary approach with an emphasis on dietary, medication and behavioral issues, using specific medications such as corticosteroids and adjuvants to alcoholism, in addition to adequate nutritional and behavioral therapy to reduce morbidity and mortality. liver transplantation, although it is still the definitive therapy, does not yet have a specific protocol for its indication.
Keywords: Alcoholic Liver Desease; Alcoholic Hepatitis; Treatment